Composition containing microspheres and cross-linked hyaluronic acid or salt thereof as well as preparation method and application of composition
The composition containing microspheres and crosslinked hyaluronic acid or its salt prepared by Semo crosslinking technology solves the problems of complex processes, residual crosslinking agents, and rapid degradation of microspheres in the prior art, and achieves the synergistic effect and safety improvement of the composition.
Patent Information
- Application Number
- CN202411738312.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The prior art cannot take into account the industrial needs of simplicity, safety, effective removal of crosslinking agents, strong viscosity, high cohesion and low water absorption of hyaluronic acid gel preparation process, and it is difficult to effectively ensure the degradation effect of microspheres and the regeneration of collagen.
Using Semo cross-linking technology, cross-linked hyaluronic acid or its salt gel is prepared first, and then mixed with microspheres. The rigid microspheres enter the gel to enhance the support performance of the soft and elastic chimeric structure and form a synergistic composition to ensure effective protection of microspheres during moisture and heat sterilization.
The synergistic effect of the soft elastic function of the composition and the rigid support performance is achieved, the degradation time of the microspheres and the effect of collagen regeneration is extended, and the safety and application range of the composition are improved.
Smart Images

Figure CN119524206A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and specifically relates to a composition containing microspheres and cross-linked hyaluronic acid or its salt, and a preparation method and application thereof. Background Art
[0002] Hyaluronic acid is a natural mucopolysaccharide, composed of (1-β-4) D-glucuronic acid and (1-β-3) N-acetyl-D-aminoglucose disaccharide units repeatedly connected. It is an important component of human and animal skin, vitreous body, joint lubricating fluid and cartilage tissue. Sodium hyaluronate has multiple functions in the human body, including: space filling, hydration, joint lubrication, and providing a matrix through which cells can migrate. Although hyaluronic acid has many advantages, the weak mechanical properties of natural hyaluronic acid and its easy degradation in the body limit its application in biomaterials. Cross-linked sodium hyaluronate is a polymer gel obtained by chemical cross-linking of sodium hyaluronate, which makes up for the short retention time of natural sodium hyaluronate.
[0003] Patent document CN106279726B discloses a cross-linked sodium hyaluronate gel and a preparation method thereof. Under ultrasonic conditions, a cross-linking agent is added dropwise to an alkaline aqueous solution of sodium hyaluronate to carry out a cross-linking reaction. After the reaction is completed, the pH value of the system is adjusted to 7.1-7.5 with an acid, stirred for 1-2 hours, and then precipitated with anhydrous ethanol to obtain a cross-linked sodium hyaluronate gel. However, this method does not have a step of removing the cross-linking agent, which easily causes the cross-linking agent to remain.
[0004] Patent document CN112940300B discloses a method for preparing a cross-linked hyaluronic acid gel, comprising the following steps:
[0005] (1) Mixing an aqueous solution containing a crosslinking agent and hyaluronic acid, a metal salt thereof, or a mixture thereof in a non-neutral environment to form a mixed solution; (2) placing the mixed solution at a temperature lower than 0°C and higher than the eutectic point of the mixed solution and maintaining the temperature for a time sufficient to form a solid-liquid heterogeneous system; (3) placing the heterogeneous system at a temperature lower than 0°C and higher than the eutectic point of the mixed solution to perform a crosslinking reaction; (4) melting the solid phase in the heterogeneous system after the crosslinking reaction, and optionally neutralizing, purifying, and homogenizing. However, the neutralization step described in this method cannot ensure that the pH of the system decreases more gently, thereby easily destroying the three-dimensional crosslinked structure of the sodium hyaluronate gel system.
[0006] Polyester microspheres, collagen microspheres, silk fibroin microspheres, hydroxyapatite microspheres, etc. are usually used as a new type of medical and aesthetic filling material due to their biocompatibility, biodegradability and non-toxicity. However, when the microspheres currently studied are mixed with carriers such as matrices and sterilized, the carriers cannot protect the microspheres well, so that after the product is injected and filled, the microspheres are still prone to problems such as rapid degradation, incompatibility with the tissues at the injection site, and inflammation.
[0007] In summary, the existing technology cannot take into account the industrialization requirements of hyaluronic acid gel, such as simple preparation process, good safety, effective removal of cross-linking agents, strong viscosity, high cohesion, and low water absorption. It is also difficult to effectively ensure the degradation effect of microspheres and achieve collagen regeneration. Summary of the invention
[0008] The present invention overcomes the defects existing in the prior art and provides a composition containing microspheres and cross-linked hyaluronic acid or its salt, and a preparation method and application thereof. Through Semo cross-linking technology (Soft Elastic Mosaic Cross-Linking Technology, abbreviated as Semo cross-linking technology), a cross-linked hyaluronic acid or its salt gel is first prepared and then mixed with microspheres. The entry of rigid microspheres into the gel can further enhance the supporting performance of the soft elastic mosaic structure, so that the composition has both the soft elastic function of the gel and the rigid supporting performance, and the two have a synergistic effect; at the same time, the gel can effectively protect the microspheres during wet heat sterilization, reduce the degradation of the microspheres, and prolong the effect of the microspheres stimulating collagen regeneration. The applicable skin layers and filling sites are more extensive, and the safety of the use of the composition is improved.
[0009] In a first aspect of the present invention, there is provided a composition comprising microspheres and cross-linked hyaluronic acid or a salt thereof, wherein the preparation method of the cross-linked hyaluronic acid or a salt thereof in the composition comprises the following steps:
[0010] (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt;
[0011] (2) mixing hyaluronic acid III or its salt, a second alkaline solution and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt;
[0012] (3) After diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, add the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mix and react to obtain the cross-linked hyaluronic acid or its salt.
[0013] Furthermore, the mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution.
[0014] Furthermore, the molecular weight of the hyaluronic acid I or its salt is higher than the molecular weight of the hyaluronic acid II, III, IV or its salt.
[0015] Further, the concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL (e.g., 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 36 mg / mL, 37 mg / mL, 38 mg / mL, 39 mg / mL, 40 mg / mL, 41 mg / mL, 42 mg / mL, 43 mg / mL, 44 mg / mL, 45 mg / mL, 46 mg / mL, 47 mg / mL, 48 mg / mL, 49 mg / mL, 50 mg / mL, 51 mg / mL, 52 mg / mL, 53 mg / mL, 54 mg / mL, 55 mg / mL, 56 mg / mL, 57 mg / mL, 58 mg / mL, 59 mg / mL, 60 mg / mL, 61 mg / mL, 62 mg / mL, 63 mg / mL, 64 mg / mL, 65 mg / mL, 66 mg / mL, 67 mg / mL, 68 mg / mL, 69 mg / mL, 70 mg / mL, 71 mg / mL, 72 mg / mL, 73 mg / mL, 74 mg / mL 7mg / mL, 48mg / mL, 49mg / mL, 50mg / mL, 51mg / mL, 52mg / mL, 53mg / mL, 54mg / mL, 55mg / mL, 56mg / mL, 57mg / mL , 58 mg / mL, 59 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL), preferably 12 to 90 mg / mL, more preferably 15 to 80 mg / mL.
[0016] Further, in step (2), the concentration of the second alkaline solution is 0.1-50 mg / mL (such as 0.1 mg / mL, 1 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, 21 mg / mL, 22 mg / mL, 23 mg / mL, 24 mg / mL, 25 mg / mL, 26 mg / mL, 27 mg / mL, 28 mg / mL, 29 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL), preferably 1-40 mg / mL, and more preferably 5-30 mg / mL.
[0017] Furthermore, the molecular weight of the hyaluronic acid I or its salt is 900-3000 kDa (such as 900 kDa, 950 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa, 2000 kDa, 2500 kDa, 3000 kDa), preferably 1000-2000 kDa, and more preferably 1200-1600 kDa.
[0018] In one embodiment of the present invention, the molecular weight of the hyaluronic acid I or its salt is 1500 kDa.
[0019] Further, the molecular weight of the hyaluronic acid II, III, IV or its salt is 100-1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300-800 kDa, and more preferably 400-700 kDa.
[0020] Furthermore, the molecular weights of the hyaluronic acid II, III, IV or their salts may be the same or different.
[0021] In one embodiment of the present invention, the molecular weight of the hyaluronic acid II, III, IV or its salt is 600 kDa.
[0022] Furthermore, in step (1), the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt is 2-10:1, preferably 3-9:1.
[0023] In one embodiment of the present invention, the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 3:1.
[0024] Furthermore, the mass ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1; preferably 2-6:1.
[0025] Furthermore, the amount of hyaluronic acid IV or its salt added is 5-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.
[0026] Furthermore, water is added in step (3) to dilute the alkaline solution to a concentration equal to the concentration of the second alkaline solution in step (2).
[0027] Furthermore, the reaction temperature in steps (1), (2) and (3) is 20 to 30°C.
[0028] Furthermore, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.
[0029] Furthermore, the reaction temperature and time in steps (1), (2) and (3) may be the same or different.
[0030] In one embodiment of the present invention, the reaction temperature in step (1) is 25° C. and the reaction time is 20 h.
[0031] Furthermore, the hyaluronic acid I or its salt, hyaluronic acid II or its salt, hyaluronic acid III or its salt and hyaluronic acid IV or its salt can be derived from animals or obtained through bacterial fermentation.
[0032] Further, the hyaluronate is selected from any one of sodium hyaluronate (HA), potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate; preferably sodium hyaluronate.
[0033] Furthermore, the alkaline solution is selected from: a solution prepared by one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, and potassium sulfite, preferably a sodium hydroxide solution. The first alkaline solution and the second alkaline solution may be the same or different; preferably, the first alkaline solution and the second alkaline solution are the same.
[0034] Furthermore, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether (BDDE), divinyl sulfone, polyethylene glycol, genipin and carbodiimide, preferably 1,4-butanediol diglycidyl ether.
[0035] Furthermore, the cross-linking degree of the cross-linked hyaluronic acid or its salt is 1% to 6%, preferably 1.5% to 5%.
[0036] Furthermore, the microspheres are selected from one or more of polyester microspheres, collagen microspheres, silk fibroin microspheres, and hydroxyapatite microspheres.
[0037] Furthermore, the microspheres are polyester microspheres.
[0038] Furthermore, the polyester is selected from one or more of left-lactic acid PLLA, right-lactic acid PDLA, racemic polylactic acid PDLLA, polylactic acid co-glycolic acid PLGA, polymethyl methacrylate PMMA, polycaprolactone PCL, left-lactic acid-ethylene glycol copolymer PEG-PLLA or hydroxyapatite-left-lactic acid HAP-PLLA.
[0039] Furthermore, the content of microspheres in the composition is: 1% to 35% (such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%), preferably 10% to 32%, and more preferably 15% to 30%.
[0040] Further, the mass concentration of the cross-linked hyaluronic acid or its salt is 1-30 mg / mL (such as 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 10.5 mg / mL, 11 mg / mL, 11.5 mg / mL, 12 mg / mL, 12.5 mg / mL, 13 mg / mL, 13.5 mg / mL, 14 mg / mL, 14.5 mg / mL, 15 mg / mL, 15.5 mg / mL, 16 mg / mL, 16.5 mg / mL, 17 mg / mL, 17.5 mg / mL, 18 mg / mL, 18.5 mg / mL, 19 mg / mL, 19.5 mg / mL, 20 mg / mL), preferably 5-25 mg / mL, more preferably 10-20 mg / mL.
[0041] The present invention firstly carries out compounding of high and low molecular weight hyaluronic acid or its salt, under the condition that the amount of alkaline solution is large, by destroying the hydrogen bonding between hyaluronic acid or its salt, the molecular chain of hyaluronic acid or its salt is fully extended and stretched, wherein the molecular chain of low molecular weight hyaluronic acid or its salt can freely carry out irregular translation or rotational motion while stretching, so that low molecular weight hyaluronic acid or its salt can be interspersed or erected between high molecular weight hyaluronic acid or its salt, realize high and low molecular weight hyaluronic acid or its salt interspersed crosslinking;Meanwhile, the amount of alkaline solution is large, and there is certain degradation effect on the molecular chain of hyaluronic acid or its salt while crosslinking, and finally forms a three-dimensional loose network structure with large mesh spacing. Subsequently, under the condition that the amount of alkaline solution is small, low molecular weight hyaluronic acid or its salt is crosslinked, the amount of alkali solution is low, the hydrogen bonding between hyaluronic acid or its salt is strong, and the molecular chain winding is relatively common, and hyaluronic acid or its salt and crosslinking agent are easy to react quickly to form a compact network structure, and obtain micron gel particles. However, due to the fact that the cross-linking reaction is not thorough enough under the condition of a large amount of alkaline solution, a part of the cross-linking agent still exists. By adding water to adjust the dilution, the condition of a large amount of alkaline solution is changed to a condition of a small amount of alkaline solution, and micron gel particles, hyaluronic acid or its salt are added to continue the reaction and consume the cross-linking agent that has not reacted completely, so that the compact structure can penetrate into the looser structure, forming a cross-linked hyaluronic acid or its salt gel with a soft elastic mosaic structure of loose pores encapsulating elastic hard balls. Since the loose pore area has good ductility, the gel has good support performance, ductility and deformation resistance, and has better water absorption and water retention, better tissue compatibility, and is more suitable for flat injection filling of the inner and outer surfaces of the cavity.
[0042] In addition, the present invention mixes the microspheres with the above-mentioned cross-linked hyaluronic acid or its salt gel. Since there are many loose pores in the gel, most of the rigid microspheres can enter the loose pores during the mixing process, thereby avoiding the agglomeration of the microspheres, making the microspheres more evenly dispersed in the soft elastic mosaic structure of the gel, and achieving the encapsulation of the microspheres to a certain extent, so that the gel can effectively protect the microspheres during wet heat sterilization, better retain the filling performance and dispersion performance of the microspheres, reduce the degradation of the microspheres, and prolong the degradation time and safety performance of the microspheres after implantation in the body; the entry of rigid microspheres can further enhance the supporting performance of the soft elastic mosaic structure, so that the composition has both the soft elastic function of the gel and the rigid supporting performance, and the two have a synergistic effect, thereby prolonging the effect of the microspheres stimulating collagen regeneration, and the applicable skin layers and filling sites are more extensive, thereby improving the safety of the use of the composition.
[0043] Furthermore, the composition further comprises non-cross-linked hyaluronic acid or a salt thereof, a phosphate buffer, an optional local anesthetic and / or a water-soluble cellulose.
[0044] Furthermore, the non-cross-linked hyaluronate is selected from any one of non-cross-linked sodium hyaluronate, non-cross-linked potassium hyaluronate, non-cross-linked calcium hyaluronate, non-cross-linked magnesium hyaluronate, non-cross-linked ammonium hyaluronate, non-cross-linked tetrabutylammonium hyaluronate, non-cross-linked bismuth hyaluronate and non-hyaluronate zinc, preferably non-cross-linked sodium hyaluronate.
[0045] Further, the concentration of the non-cross-linked hyaluronic acid or its salt is 0.2-10 mg / mL (such as 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably 0.5-8 mg / mL, more preferably 1-6 mg / mL.
[0046] Further, the molecular weight of the non-cross-linked hyaluronic acid or its salt is 100-1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300-800 kDa, and more preferably 400-700 kDa.
[0047] Furthermore, the phosphate buffer comprises: disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride.
[0048] Further, the concentration of the sodium hydrogen phosphate is 0.01 to 10 mg / mL (e.g., 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL). , 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably, the concentration of the sodium hydrogen phosphate is 3 to 10 mg / mL, more preferably, the concentration of the sodium hydrogen phosphate is 4 to 8 mg / mL.
[0049] In one embodiment of the present invention, the concentration of disodium hydrogen phosphate is 10 mg / mL.
[0050] Further, the concentration of the sodium dihydrogen phosphate is 0.01-9 mg / mL (such as 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.5, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL, 7.5 mg / mL, 8 mg / mL, 8.5 mg / mL, 9 mg / mL), preferably, the concentration of the sodium dihydrogen phosphate is 1-7 mg / mL, further preferably, the concentration of the sodium dihydrogen phosphate is 2-6 mg / mL.
[0051] In one embodiment of the present invention, the concentration of sodium dihydrogen phosphate is 4 mg / mL.
[0052] Further, the concentration of potassium chloride is 0.01-7 mg / mL (such as 0.01 mg / mL, 0.02 mg / mL, 0.03 mg / mL, 0.04 mg / mL, 0.05 mg / mL, 0.06 mg / mL, 0.07 mg / mL, 0.08 mg / mL, 0.09 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, 1.5 mg / mL). L, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.5, 3 mg / mL, 3.5, 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL, 6 mg / mL, 6.5 mg / mL, 7 mg / mL), preferably, the concentration of potassium chloride is 0.05-5 mg / mL, more preferably, the concentration of potassium chloride is 0.1-3 mg / mL.
[0053] In one embodiment of the present invention, the concentration of potassium chloride is 1 mg / mL.
[0054] Furthermore, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof.
[0055] Further, the local anesthetic is selected from: lidocaine or its salt, bupivacaine or its salt, butancaine or its salt, carticaine or its salt, cinchocaine or its salt, chlorocaine or its salt, ethyl p-piperidylacetylaminobenzoate or its salt, etidocaine or its salt, mepivacaine or its salt, oxethicaine or its salt, prilocaine or its salt, ropivacaine or its salt, tolicaine or its salt, trimecaine or its salt, vardocaine or its salt, articaine or its salt, levobupivacaine or its salt, amicaine or its salt, cocaine or its salt, The group consisting of one or more of propancaine or its salt, chloroparacaine or its salt, cyclomethicaine or its salt, proparacaine or its salt, tetracaine or its salt, benzocaine or its salt, butacaine or its salt, butyrocaine or its salt, butylaminobenzoate or its salt, chloroprocaine or its salt, dimethocaine or its salt, oxybuprocaine or its salt, piperocaine or its salt, ethoxycaine or its salt, procaine or its salt, propoxycaine or its salt, tricaine or its salt, preferably lidocaine or its salt, more preferably lidocaine hydrochloride.
[0056] Further, the content range of the local anesthetic is 0.1-10 mg / mL (such as 0.1 mg / mL, 0.2 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL), preferably, the content range of the local anesthetic is 0.1-8 mg / mL, further preferably, the content range of the local anesthetic is 0.5-8 mg / mL, and even more preferably, the content range of the local anesthetic is 0.5-5 mg / mL.
[0057] In one embodiment of the present invention, the content of the local anesthetic is in the range of 3 mg / mL.
[0058] Furthermore, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose, preferably hydroxypropyl methylcellulose.
[0059] Furthermore, the content of the water-soluble cellulose is in the range of 0.01 to 40 mg / mL, preferably 0.2 to 25 mg / mL, and more preferably 0.5 to 10 mg / mL.
[0060] The second aspect of the present invention provides a method for preparing a composition containing microspheres and cross-linked hyaluronic acid or a salt thereof, comprising the following steps:
[0061] The cross-linked hyaluronic acid or its salt is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is slowly adjusted to neutral with a lactic acid solution, and then the microspheres are added, mixed evenly, and sterilized by wet heat to obtain the composition.
[0062] Furthermore, after adjusting the pH value of the system to neutral, phosphate buffer, non-cross-linked hyaluronic acid or its salt, and optionally local anesthetic and / or water-soluble cellulose may be added.
[0063] The third aspect of the present invention provides an application of the composition containing microspheres and cross-linked hyaluronic acid or its salt described in the first aspect or the composition containing microspheres and cross-linked hyaluronic acid or its salt prepared in the second aspect in the preparation of medicines, tissue engineering materials, and cosmetics.
[0064] Preferably, the tissue engineering material includes soft tissue filling material, cartilage repair material, and tissue engineering scaffold.
[0065] The fourth aspect of the present invention provides a non-medical cosmetic use of the composition containing microspheres and cross-linked hyaluronic acid or its salt as described in the first aspect or the composition containing microspheres and cross-linked hyaluronic acid or its salt prepared in the second aspect, for improving the appearance of the skin, smoothing wrinkles or repairing the appearance of the face or body of a subject.
[0066] A fifth aspect of the present invention provides a non-medical method for improving the appearance of skin, smoothing wrinkles, or reshaping the face or body of a subject, comprising:
[0067] I) providing a composition containing microspheres and cross-linked hyaluronic acid or a salt thereof as described in the first aspect or a composition containing microspheres and cross-linked hyaluronic acid or a salt thereof prepared in the second aspect, and
[0068] II) injecting the composition containing microspheres and cross-linked hyaluronic acid or its salt as described in the first aspect or the composition containing microspheres and cross-linked hyaluronic acid or its salt prepared in the second aspect into the skin of a subject.
[0069] Furthermore, the composition containing microspheres and cross-linked hyaluronic acid or its salt in step II is injected into the dermis and / or subcutaneous tissue.
[0070] Beneficial effects of the present invention:
[0071] (1) The present invention is to compound high and low molecular weight hyaluronic acid or its salt, under the condition of large amount of alkaline solution, by destroying the hydrogen bonding between hyaluronic acid or its salt, so that the molecular chain of hyaluronic acid or its salt is fully extended and stretched, and low molecular weight hyaluronic acid or its salt can be interspersed or erected between high molecular weight hyaluronic acid or its salt while stretching, so as to realize the interspersed crosslinking of high and low molecular weight hyaluronic acid or its salt; at the same time, the amount of alkaline solution is large, and there is a certain degradation effect on the molecular chain of hyaluronic acid or its salt while crosslinking, and finally form a three-dimensional loose network structure with a large mesh spacing. Subsequently, under the condition of small amount of alkaline solution, low molecular weight hyaluronic acid or its salt is crosslinked, the amount of alkali solution is low, the hydrogen bonding between hyaluronic acid or its salt is strong, the molecular chain entanglement is relatively common, and hyaluronic acid or its salt and crosslinking agent are easy to react quickly to form a compact network structure, so as to obtain micron gel particles. However, due to the incomplete cross-linking reaction under the condition of large amount of alkali solution, a part of cross-linking agent still exists. By adding water to adjust the dilution, the condition of large amount of alkali solution is changed to that of small amount of alkali solution, and micron gel particles, hyaluronic acid or its salt are added to continue the reaction and consume the incompletely reacted cross-linking agent, so that the compact structure can penetrate into the looser structure to form a cross-linked hyaluronic acid or its salt gel with a soft elastic mosaic structure of loose pores wrapping elastic hard balls. Since the loose pore area has good ductility, the gel has good supporting performance, ductility and anti-deformation performance, and has better water absorption and water retention.
[0072] (2) The present invention mixes microspheres with the above-mentioned cross-linked hyaluronic acid or its salt gel. Since the above-mentioned gel has many loose pores, most of the rigid microspheres can enter the loose pores during the mixing process, thereby avoiding the agglomeration of the microspheres and making the microspheres more evenly dispersed in the soft elastic mosaic structure of the gel. The microspheres are also wrapped to a certain extent, so that the gel can effectively protect the microspheres during wet heat sterilization, better retain the filling performance and dispersion performance of the microspheres, reduce the degradation of the microspheres, and prolong the degradation time and safety performance of the microspheres after implantation in the body, thereby prolonging the effect of the microspheres stimulating collagen regeneration. The entry of rigid microspheres can further enhance the supporting performance of the soft elastic mosaic structure, so that the composition has both the soft elastic function of the gel and the rigid supporting performance. The two have a synergistic effect, and are applicable to a wider range of skin layers and filling sites, thereby improving the safety of the use of the composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 This is a schematic electron microscope diagram of the composition of Example 1.
[0074] Figure 2Schematic diagram of the compositions of Example 1 and Comparative Example 4 before and after centrifugation (Left 1: the composition of Comparative Example 4 before centrifugation, Left 2: the composition of Example 1 before centrifugation, Right 1: the composition of Comparative Example 4 after centrifugation, Right 2: the composition of Example 1 after centrifugation). DETAILED DESCRIPTION
[0075] In order to more clearly understand the technical content of the present invention, the following embodiments are given in detail, the purpose of which is only to better understand the content of the present invention but not to limit the protection scope of the present invention.
[0076] The raw materials and reagents used in the examples and comparative examples are all commercially available.
[0077] Example 1
[0078] (1) Preparation of cross-linked sodium hyaluronate I′: Take 1.5 g of 1500 kDa sodium hyaluronate raw material, take 0.5 g of 600 kDa sodium hyaluronate raw material, add 20 mL of water, add 5 mL of 250 mg / mL sodium hydroxide solution, add 0.06 mL of BDDE solution, mix well, react at 25° C. for 20 h, and obtain cross-linked sodium hyaluronate I′.
[0079] (2) Preparation of cross-linked sodium hyaluronate II′: Take 0.6 g of 600 kDa sodium hyaluronate raw material, add 6 mL of water, add 1.5 mL of 100 mg / mL sodium hydroxide solution to dissolve, add 0.03 mL of BDDE solution, mix well, react at 25°C for 20 h, and make the gel into micron particles to obtain cross-linked sodium hyaluronate II′.
[0080] (3) Preparation of cross-linked sodium hyaluronate: Add 37.5 mL of water to the cross-linked sodium hyaluronate I′ of step (1), stir evenly, add the micronized particles of cross-linked sodium hyaluronate II′ of step (2) and 0.3 g of 600 kDa sodium hyaluronate raw material to the cross-linked sodium hyaluronate I′, mix evenly, and continue the reaction at 25° C. for 6 h. After the reaction is completed, cross-linked sodium hyaluronate is obtained.
[0081] (4) The cross-linked sodium hyaluronate obtained in step (3) is dialyzed and the pH value of the system is first adjusted to about 10-11 with a hydrochloric acid solution having a mass concentration of 8%, and then the pH value of the system is slowly adjusted to neutral with a 30% lactic acid solution. Subsequently, 100 mL of phosphate buffer (10 g of disodium hydrogen phosphate, 4 g of sodium dihydrogen phosphate, and 1 g of potassium chloride are weighed and dissolved in 1000 mL of water), 0.58 g of lidocaine hydrochloride, 0.4 g of 600 kDa sodium hyaluronate, and 34.9 g of L-lactic acid-ethylene glycol copolymer microspheres are added, and water is added to 194 mL, mixed evenly, and sterilized by wet heat to obtain a cross-linked sodium hyaluronate gel composition (the theoretical molar cross-linking degree of the combination group is 7.5%), which is defined as Composition 1.
[0082] Example 2
[0083] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 900 kDa, and 600 kDa was replaced by 300 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 300 kDa, and the remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%), to obtain composition 2.
[0084] Example 3
[0085] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 2800 kDa, and 600 kDa was replaced by 1000 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 1000 kDa, and the remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%), to obtain composition 3.
[0086] Example 4
[0087] Only the volume of 5 mL of sodium hydroxide in step (1) of Example 1 was replaced by 2 mL, and the volume of 1.5 mL of sodium hydroxide in step (2) was replaced by 0.6 mL, and the remaining steps were the same as in Example 1 (the theoretical molar crosslinking degree of the combination group was 7.5%), to obtain composition 4.
[0088] Example 5
[0089] Only 34.9 g of L-lactic acid-ethylene glycol copolymer microspheres in step (4) of Example 1 were replaced with 9.7 g of hydroxyapatite microspheres, and lidocaine hydrochloride was not added. The remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%), to obtain composition 5.
[0090] Example 6
[0091] Only 34.9 g of L-lactic acid-ethylene glycol copolymer microspheres in step (4) of Example 1 were replaced with 58.2 g of L-polylactic acid microspheres, and 0.15 g of hydroxypropyl methylcellulose was added. The remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%), to obtain composition 6.
[0092] Comparative Example 1
[0093] Only the step (1) of Example 1 in which "adding 5 mL of 250 mg / mL sodium hydroxide solution" is replaced by "adding 5 mL of 100 mg / mL sodium hydroxide solution" is replaced, and the remaining steps are the same as Example 1 (the theoretical molar crosslinking degree of the combination group is 7.5%), is obtained to obtain a comparative composition 1.
[0094] Comparative Example 2
[0095] Only the step (1) of Example 1 in which "take 1.5 g of 1500 kDa sodium hyaluronate raw material and 0.5 g of 600 kDa sodium hyaluronate raw material" is replaced with "take 2 g of 1500 kDa sodium hyaluronate raw material", and the remaining steps are the same as Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%), is obtained to obtain comparative composition 2.
[0096] Comparative Example 3
[0097] Only the step (1) of Example 1 in which "take 1.5 g of 1500 kDa sodium hyaluronate raw material and 0.5 g of 600 kDa sodium hyaluronate raw material" is replaced with "take 2 g of 600 kDa sodium hyaluronate raw material", and the remaining steps are the same as Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%), is obtained to obtain comparative composition 3.
[0098] Comparative Example 4
[0099] Preparation of cross-linked sodium hyaluronate gel: Take 2.9 g of 1500 kDa sodium hyaluronate raw material, add 20 mL of water, add 12.5 mL of 20 mg / mL sodium hydroxide solution to dissolve, add 0.1 mL of BDDE solution, mix well, react at 25° C. for 30 h to obtain a cross-linked sodium hyaluronate gel. Then, the gel composition was prepared in the same manner as in Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%) to obtain comparative composition 4.
[0100] Performance Testing
[0101] Performance example 1
[0102] The composition of Example 1 was freeze-dried and observed using a scanning electron microscope. The structure of the composition is as follows: Figure 1 As shown. Figure 1 It can be seen that the microspheres are uniformly dispersed in the network mosaic structure of the composition, and the loose network structure forms a good encapsulation for most of the microspheres.
[0103] Performance example 2
[0104] Samples of the compositions of Example 1 and Comparative Example 4 were taken and subjected to high-speed centrifugation. After standing for 10 minutes, the stratification phenomenon of the compositions was observed to evaluate the stability of the compositions.
[0105] from Figure 2It can be seen that before centrifugation, the compositions of Example 1 and Comparative Example 4 are milky white gels as a whole, without stratification, indicating that the microspheres are uniformly dispersed in the gel. After centrifugation, the composition of Example 1 only slightly separated the gel from the microspheres, and only a small part of the microspheres sank to the bottom of the test tube, and most of the microspheres were still dispersed in the gel, indicating that the cross-linked sodium hyaluronate of Example 1 has better encapsulation of the L-lactic acid-ethylene glycol copolymer microspheres in the composition, so that the microspheres can be better suspended and dispersed in the gel, and the stability is better; while the composition of Comparative Example 4 after centrifugation, there was a clear phenomenon of separation of the gel from the microspheres, and a large number of microspheres sank to the bottom of the test tube, indicating that the gel failed to well encapsulate the microspheres and enable them to be stably suspended and dispersed in the gel, and also indicated that the conventional cross-linked sodium hyaluronate mixed microspheres are prone to poor long-term storage stability.
[0106] Performance Example 3
[0107] The performance of the composition samples of the embodiments and comparative examples was tested, including elastic modulus and crosslinking degree. The specific testing methods are as follows:
[0108] Elastic modulus: 2 g of the composition samples were taken respectively, and the modulus of the composition samples before and after moist heat sterilization was tested using a rheometer (TA) at 25° C. and a frequency of 1 Hz.
[0109] Cross-linking degree: Take the cross-linked sodium hyaluronate samples prepared by step (3) in Examples 1-6 and Comparative Examples 1-3, and 12 g of the cross-linked sodium hyaluronate sample in Comparative Example 4, add 200 g of ethanol, stir and mix, and let stand to precipitate. Collect the precipitate, dry it at 80°C, degrade it with 2 mL of 0.5 mol / L sulfuric acid solution at 100°C until the solution is transparent, neutralize it with 1 mol / L sodium hydroxide, and then freeze-dry it. Deuterated DMSO is used as the solvent, and hydrogen nuclear magnetic resonance is used to determine the molar cross-linking degree according to the area normalization method. The cross-linking degree = [δ = 1.5 peak area / 4] / [δ = 1.9 peak area / 3], where the peak at 1.5 ppm represents the (-methene-) group of the BDDE molecule, and the peak at 1.9 ppm represents the n-acetylglucosamine in the cross-linked sodium hyaluronate gel.
[0110] The characterization results are shown in Table 1.
[0111] Table 1 Elastic modulus and crosslinking degree results of different samples
[0112]
[0113] As can be seen from Table 1, the crosslinking efficiency in Examples 1-6 is relatively high, all reaching more than 65%, and the modulus loss rate is low, so the embodiments 1-6 can better withstand wet heat sterilization treatment and maintain stability. This is mainly because in the present invention, high and low molecular weight HA are formed into a loose network structure under the condition of a large amount of alkaline solution, and then under the condition of a small amount of alkaline solution, low molecular weight HA is used as a raw material. Since the hydrogen bonding between HA is strong, the molecular chain entanglement is more common, and it is easy to react quickly to form a compact network structure to obtain micron gel particles, and the first crosslinking product with a large amount of alkaline solution is diluted by adding water to adjust the dilution, so that the condition of a large amount of alkaline solution is changed to a condition of a small amount of alkaline solution, and then the micron gel particles and HA are added to continue the reaction, so that the compact structure penetrates into the looser structure to form a crosslinked HA gel with a soft elastic mosaic structure of loose pores wrapping elastic hard balls; and by controlling the amount of alkali and the coordination of molecular weight, the crosslinking reaction efficiency can be improved while controlling the network structure, so the final crosslinking efficiency is high. Subsequently, the cross-linked HA gel is mixed with microspheres, etc. Since the above gel has many loose pores, the microspheres can enter the loose pores during the mixing process, achieving a certain degree of encapsulation of the microspheres. The entry of rigid balls further enhances the supporting performance of the soft elastic mosaic structure, so that the composition has both the soft elastic function of the gel and the rigid supporting performance. The two can play a synergistic effect, further improving the overall structural stability of the gel, so that it can withstand wet heat sterilization, and the loss rate of elastic modulus after sterilization is low.
[0114] The crosslinking efficiency and modulus loss rate of Comparative Examples 1-4 are significantly inferior to those of Example 1. This is also because the amount of alkali in Comparative Example 1 is the same, and it is difficult to form an interpenetrating chimeric structure, which affects the synergistic effect of the microspheres and the chimeric structure, so its modulus loss rate is high; in Comparative Examples 2-3, since the molecular weight of the HA raw material during the first crosslinking is a single molecular weight, it is difficult to form a loose network structure, and it is difficult for the microspheres to enter the network structure, resulting in poor dispersion of the microspheres and easy aggregation, so its modulus loss rate is high; in Comparative Example 4, under conventional single molecular weight conditions, crosslinking mostly occurs between parallel chains, the crosslinked network is relatively dense, the mesh spacing is small, and the microspheres cannot enter the interior of the gel structure. Therefore, the composition has poor protection for the microspheres during wet heat sterilization, and the overall elastic modulus loss rate is high.
[0115] Performance example 4
[0116] The pH value and degradation performance of the composition samples of the embodiments and comparative examples were tested, and the specific testing methods are as follows:
[0117] pH value: Take 3.0 g of the composition, dilute it with water in an equal mass ratio, and use a pH meter to measure the pH value before and after moist heat sterilization.
[0118] Degradation performance: Take 10 g of the composition of Examples 1-4, 6 and Comparative Examples 1-4, add 20 mL of 1 mol / L hydrochloric acid solution, and degrade at 70°C. Replace the hydrochloric acid solution every 2 days and observe the time it takes for the composition to be completely degraded.
[0119] Take 10 g of the composition of Example 5, add 20 mL of a phosphate buffer solution of pH 4.0, and degrade at 80° C. to observe the time it takes for the composition to be completely degraded.
[0120] The characterization results are shown in Table 2.
[0121] Table 2 pH and degradation performance results of different samples
[0122] Project Name pH value before sterilization pH after sterilization pH change rate Degradation performance (d) Example 1 7.25 7.18 -0.07 42 Example 2 7.26 7.12 -0.14 38 Example 3 7.25 7.11 -0.14 39 Example 4 7.24 7.11 -0.13 38 Example 5 7.27 7.31 +0.04 37 Example 6 7.25 7.07 -0.18 46 Comparative Example 1 7.24 7.05 -0.19 37 Comparative Example 2 7.25 7.04 -0.21 37 Comparative Example 3 7.27 7.06 -0.21 36 Comparative Example 4 7.26 7.05 -0.21 36
[0123] From the results in Table 2, it can be seen that the samples of Examples 1-4 and 6 of the present invention have high cross-linking efficiency, small pH value changes, and long microsphere degradation time. The degradation time of the microspheres in Example 1 is 42 days, which is higher than that in Comparative Examples 1-4. This is because the cross-linked sodium hyaluronate in Example 1 has a soft elastic intercalated structure. The cross-linked sodium hyaluronate is mixed with the microspheres. Since there are many loose pores in the above gel, a part of the rigid microspheres can enter the loose pores during the mixing process, thereby avoiding the agglomeration of the microspheres, making the microspheres more evenly dispersed in the soft elastic intercalated structure of the gel, and achieving the encapsulation of the microspheres to a certain extent, effectively protecting the microspheres during wet heat sterilization, better retaining the filling performance and dispersion performance of the microspheres, reducing the degradation of the microspheres, and thus sterilizing. The pH change after crosslinking is small, and the degradation time is long; while in Comparative Example 1, the amount of alkali is the same, and it is difficult to form an interpenetrating chimeric structure, which affects the synergistic effect of the microspheres and the chimeric structure; in Comparative Examples 2-3, since the molecular weight of the HA raw material during the first crosslinking is a single molecular weight, it is difficult to form a loose network structure, and it is difficult for the microspheres to enter the loose network structure, resulting in poor dispersion of the microspheres and easy aggregation. Therefore, the protective effect on the microspheres is reduced; in Comparative Example 4, under conventional single molecular weight conditions, crosslinking mostly occurs between parallel chains, the crosslinked network is relatively dense, the mesh spacing is small, and the microspheres cannot enter the interior of the gel structure. Therefore, the composition has poor protection for the microspheres during wet heat sterilization. Therefore, the overall pH change rate of the composition in Comparative Examples 1-4 is high and the degradation time is short.
[0124] In addition, the microspheres added in Example 5 are hydroxyapatite, and those skilled in the art know that since hydroxyapatite contains more hydroxyl groups, the microspheres are alkaline, and if they degrade during wet heat sterilization, their degradation products will increase the pH of the system. Example 5 shows that the pH of the composition of gel mixed with hydroxyapatite microspheres prepared by the present invention only increased by 0.04 after wet heat sterilization, and the pH change rate was small, which further proves that the composition of the present invention can well protect the microspheres and reduce the degradation of the microspheres. At the same time, the degradation time of the composition of Example 5 is 37 days, indicating that the composition prepared by the process of the present invention effectively prolongs the degradation time of the microspheres after implantation in the body and the filling effect of the microspheres.
[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composition comprising microspheres and cross-linked hyaluronic acid or a salt thereof, characterized in that: The composition comprises cross-linked hyaluronic acid or its salt, and microspheres; the preparation method of the cross-linked hyaluronic acid or its salt comprises the following steps: (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt; (2) mixing hyaluronic acid III or its salt, a second alkaline solution and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt; (3) diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, adding the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mixing and reacting to obtain the cross-linked hyaluronic acid or its salt; The mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution; the molecular weight of the hyaluronic acid I or its salt is higher than the molecular weight of the hyaluronic acid II, III, IV or its salt.
2. The composition according to claim 1, characterized in that The concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL, preferably 12 to 90 mg / mL, and more preferably 15 to 80 mg / mL; the concentration of the second alkaline solution in step (2) is 0.1 to 50 mg / mL, preferably 1 to 40 mg / mL, and more preferably 5 to 30 mg / mL.
3. The composition according to claim 1, characterized in that The molecular weight of the hyaluronic acid I or its salt is 900-3000 kDa, preferably 1000-2000 kDa, more preferably 1200-1600 kDa; the molecular weight of the hyaluronic acid II, III, IV or its salt is 100-1000 kDa, preferably 300-800 kDa, more preferably 400-700 kDa.
4. The composition according to any one of claims 1 to 3, characterized in that The mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 2-10:1, preferably 3-9:1; Preferably, the ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1, preferably 2-6:
1.
5. The composition according to any one of claims 1 to 3, characterized in that The amount of hyaluronic acid IV or its salt added is 5-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.
6. The composition according to any one of claims 1 to 3, characterized in that The reaction temperature in steps (1), (2) and (3) is 20 to 30° C.; preferably, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.
7. The composition according to any one of claims 1 to 3, characterized in that The hyaluronate is selected from any one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate, preferably sodium hyaluronate; Preferably, the degree of cross-linking of the obtained cross-linked hyaluronic acid or its salt is 1% to 6%, preferably 1.5% to 5%; Preferably, the alkaline solution is selected from: a solution prepared by one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, and potassium sulfite, more preferably a sodium hydroxide solution; Preferably, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether, divinyl sulfone, polyethylene glycol, genipin and carbodiimide, more preferably 1,4-butanediol diglycidyl ether.
8. The composition according to any one of claims 1 to 3, characterized in that The microspheres are selected from one or more of polyester microspheres, collagen microspheres, silk fibroin microspheres and hydroxyapatite microspheres; preferably polyester microspheres; more preferably, the polyester microspheres are selected from one or more of PLLA, PDLA, PDLLA, PLGA, PMMA, PCL, PEG-PLLA and HA-PLLA.
9. The composition according to any one of claims 1 to 3, characterized in that The content of microspheres in the composition is 1% to 35%, preferably 10% to 32%, more preferably 15% to 30%; Preferably, the mass concentration of the cross-linked hyaluronic acid or its salt is 1 to 30 mg / mL.
10. The composition according to any one of claims 1 to 3, characterized in that The composition further comprises non-cross-linked hyaluronic acid or a salt thereof, a phosphate buffer, and optionally a local anesthetic and / or a water-soluble cellulose; Preferably, the phosphate buffer comprises disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride; Preferably, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof; Preferably, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose.
11. A method for preparing the composition according to any one of claims 1 to 10, comprising the steps of: The cross-linked hyaluronic acid or its salt is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is adjusted to neutral with a lactic acid solution, and then microspheres are added, mixed, and sterilized by wet heat to obtain a composition containing microspheres and cross-linked hyaluronic acid or its salt.
12. The preparation method according to claim 11, characterized in that: After adjusting the pH value of the system to neutral, phosphate buffer, non-cross-linked hyaluronic acid or its salt, and optionally local anesthetic and / or water-soluble cellulose may be added.
13. Use of the composition according to any one of claims 1 to 10 or the composition prepared by the preparation method according to any one of claims 11 to 12 in the preparation of medicines, tissue engineering materials or cosmetics; Preferably, the tissue engineering material comprises a soft tissue filling material, a cartilage repair material or a tissue engineering scaffold.
Citation Information
Patent Citations
Cross-linked sodium hyaluronate gel and its preparation method
CN106279726B
Preparation method of cross-linked hyaluronic acid gel
CN112940300B
Injection amphiphilic-microsphere-containing hyaluronic acid mixed gel and preparation method thereof
CN105126166A
L-polylactide filler for injection and preparation method thereof
CN105879124A
Preparation method and application of cross-linked hyaluronic acid gel for injection
CN111643730A
Cited By
Composition comprising microspheres and crosslinked hyaluronic acid or salt thereof, and preparation method therefor and use thereof
WO2026113956A1